Vinorelbine With or Without Thiotepa for HER2‐Negative Metastatic Breast Cancer: A Propensity Score Analysis - Aurelia Robert; Paul Gougis; Elise Dumas; Rebecca Loison; Victoire De Castelbajac; Marc Espie; Sylvie Giacchetti; Caroline Cuvier; Lamia Hassani; Johanna Wassermann; Luca Campedel; Marianne Veyri; et al. (Cancer Medicine)
ABSTRACT Background Vinorelbine is commonly used to treat metastatic breast cancer (mBC), while thiotepa is known for its ability to cross the blood–brain barrier. Methods Our retrospective study aimed to compare the efficacy and safety of vinorelbine with or without thiotepa in patients with HER2‐negative mBC. We used propensity score inverse probability of treatment weighting to ensure comparability between groups. Results Vinorelbine‐thiotepa was not significantly associated with improved median progression‐free survival (PFS) (4.9 vs. 3.0 months, p = 0.138) or median overall survival (OS) (11.8 vs. 11.9 months, p = 0.961) compared to vinorelbine. However, in the central nervous system (CNS) metastasis subgroup, vinorelbine‐thiotepa was associated with a longer median PFS (4.9 vs. 2.1 months, p = 0.013) and CNS‐PFS (6.12 vs. 2.20 months, p = 0.007). The combination was also associated with a higher rate of grade ≥ 3 adverse events (54.3% vs. 37.9%, p = 0.021). Conclusion While no overall benefit in PFS or OS was found, vinorelbine‐thiotepa may be associated with improved PFS in mBC patients with CNS metastasis.